THE FORMATION OF THE MAINTENANCE PROGRAM AND ITS IMPACT ON THE INCREASED LEVEL OF POWER PLANTS RELIABILITY - Adamović, Živoslav; Ivic, Mladen; Vuković, Veljko (Journal of process management and new technologies, 2020)
The paper emphasizes the basic attitudes of complex technical system maintenance programming. Particularly it is performed an analysis and a selection of strategies for condition-based maintenance. The assessment of the established maintenance program varieties effectiveness was carried out by comparison with their basic indicators of effectiveness (for corrective and preventive maintenance).